Internal Locus of Control Self Efficacy and Career Maturity: Lokus Kontrol Internal, Keyakinan Diri, dan Kematangan Karier - Herlina Dewanti; Nurfi Laili (Academia Open, 2025)
General Background: Career maturity is a crucial developmental task for vocational high school students as they prepare to enter the workforce. Specific Background: Empirical findings indicate that many students demonstrate moderate to low levels of career maturity, particularly in career planning and decision making. Psychological factors such as internal locus of control and self-efficacy are theoretically linked to students’ readiness to manage career development tasks. Knowledge Gap: Although previous studies have examined these variables separately, limited research has analyzed their simultaneous relationship within a specific vocational school context. Aims: This study aims to analyze the relationship between internal locus of control and self-efficacy with career maturity among vocational high school students at SMK X in Sidoarjo. Results: Using a quantitative correlational design with 264 respondents, the findings reveal a significant simultaneous relationship between internal locus of control and self-efficacy with career maturity (Sig. F Change = 0.000 < 0.05; R = 0.881; R² = 0.777). Novelty: The study provides contextualized empirical evidence within a single vocational school, offering a focused analysis of internal psychological predictors of career maturity. Implications: Strengthening students’ internal locus of control and self-efficacy through structured career guidance programs may support the development of more mature career planning and decision-making processes. Keywords: Internal Locus of Control, Self Efficacy, Career Maturity, Vocational High School Students, Career Development Key Findings Highlights: Simultaneous analysis reveals strong statistical association among the three measured constructs. Psychological belief in personal agency aligns with higher readiness for occupational planning. Confidence in personal capability corresponds with stronger preparation for vocational decision processes.